“La gran colecta para Jerusalén” o “La gracia y el dinero” : (Rom 15, 25-31; 2Cor 8-9) - Fernández, Víctor Manuel (1996)
Fil: Fernández, Víctor Manuel. Pontificia Universidad Católica Argentina; Argentina